The relative contributions of clinical and socio-cultural factors to treatment delay among patients with schizophrenia in south-east Nigeria - Paul Chigozie Odinka, Dr. (International Journal of Psychosocial Rehabilitation, 2015)
The study aimed to determine the relative contributions of clinical and socio-cultural factors to treatment delay among pa- tients with schizophrenia. A cross-sectional study of 360 patients who had no previous contact with psychiatric services. All factors associated with long duration of untreated psychosis (DUP) in univariate analyses at the significant level of p <0.05 were entered into a regression model to explore their association with long DUP. For each unit increase in belief in the magico-spiritual cause of schizophrenia, the odds for treatment delay increased by approximately five times; and for each unit increase in the negative symptoms, the odds for treatment delay increased by approximately three times. Cultur- ally influenced beliefs about the causes of schizophrenia, and the perceptions of its symptoms could independently and sub- stantially influence the first choice of treatment, and this could also substantially contribute to treatment delay.